Penguatan Kompetensi Guru Abad 21: Pendampingan Penerapan Model TPACK di Sekolah Dasar" - Nurratri Kurnia Sari; Andriyanto; Sukarno; Muhlis Fajar Wicaksana (Educate: Journal of Community Service in Education, 2025)
The transformation of education in the digital era requires teachers to integrate technology effectively in the learning process. The TPACK (Technological Pedagogical and Content Knowledge) model is an important framework to equip teachers to combine mastery of technology, pedagogy, and learning content. This community service activity aims to provide intensive assistance to elementary school teachers in understanding and applying the TPACK model in learning planning and implementation. The implementation method includes socialization of the TPACK concept, workshop on the preparation of TPACK-based lesson plans, and assistance in its implementation. The results of the activity showed that teachers experienced an increase in conceptual understanding and were able to apply the TPACK approach in learning that was more interactive, contextual, and learning content.